1994
DOI: 10.1111/j.1365-2265.1994.tb02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid hormone autoantibodies in healthy subjects

Abstract: These results indicate that the occurrence of thyroid hormone autoantibodies among the healthy Japanese population is fairly common. However, interference of thyroid hormone autoantibodies in the radioimmunoassay of free thyroid hormones is exceptional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 27 publications
0
33
0
3
Order By: Relevance
“…[4][5][6][7][8]15,19 This study suggests that the diagnosis of an autoimmune disorder has to be made cautiously taking into consideration that autoantibodies are present in low titres in the healthy population. The normal ranges for common autoantibodies that we have established for the Omani population may be a useful guide for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8]15,19 This study suggests that the diagnosis of an autoimmune disorder has to be made cautiously taking into consideration that autoantibodies are present in low titres in the healthy population. The normal ranges for common autoantibodies that we have established for the Omani population may be a useful guide for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…As três principais classes de anticorpos que causam interferência nos imunoensaios dos HTs são os auto-anticorpos, os anticorpos heterófilos e o fator reumatóide. Os auto-anticorpos incluem os anticorpos anti-tireoglobulina, antitireoperoxidase, anti-receptor de TSH e os anticorpos anti-T 4 e T 3 (THAAb) (116,117). Os últimos (THAAb) são os mais raros, porém os únicos que interferem nos testes de função tireoidiana (118).…”
Section: Fatores Interferentes Nos Ensaios De T 4 E T 3 Total E Livreunclassified
“…observed (7). Sakata et al (1994) screened 880 apparently healthy adults and reported that the incidence of anti-T3 or anti-T4 antibodies was 1.8% (4). The minimal effect of the antibodies on assays in these individuals could apparently be due to the lower association constants of these antibedles as compared to those used in the immunoassays.…”
Section: Adddress Forcorrespondencementioning
confidence: 99%
“…It is very rare that such autoantibodies are generated against the thyroid hormones themselves (2,3). The presence of these antibodies in serum does not onty complicate the clinical manifestations of the disease but also interferes with the estimation of total and free hormones by immuno assay (3,4,5). Their presence may be indicated when very low (undetectable) values of either or both T3 and T4 are observed in a competitive RINEIA that uses precipitation for the separation of" bound and free ligand (6).…”
mentioning
confidence: 99%